STUDY OF THE REPRODUCTION OF THE INDIGENOUS SHOR POPULATION OF THE KEMEROVO REGION - Фаина Анисимовна Лузина; Анастасия Викторовна Дорошилова; Ольга Николаевна Гуляева (Медицина в Кузбассе, 2018)
The objective was to study the dynamics of the population number and the reproduction of the indigenous Shorian population of the Kemerovo Region.